GE_GERICHTE A/3369/2006 vom 15. Dezember 2008 - GE Cour de justice (2008)
; RACHAT(ASSURANCE) ; PRÉVOYANCE PROFESSIONNELLE SELON LA LPP ; PRÉVOYANCE PROFESSIONNELLE; REVENU ACQUIS EN COMPENSATION(DROIT FISCAL) | LIPP-V. 2; LPP. 79b. al3;